الإنتماء المدرسي وعلاقته ببعض المشكلات السلوكية لدى عينة من طلبة الصف الثاني الثانوي العام بمدينة دمشق - الصياح، محمد ربيع إدريس (جامعة البعث, 2019)
هدف البحث إلى تعرف مستوى الانتماء المدرسي لدى عينة من طلبة الصف الثاني الثانوي. ودرجة انتشار المشكلات السلوكية لدى عينة من طلبة الصف الثاني الثانوي. وتعرف العلاقة بين الانتماء المدرسي والمشكلات السلوكية. وتعرف الفروق بين إجابات أفراد عينة البحث على مقياس الانتماء الاجتماعي ومقياس المشكلات السلوكية تبعا لمتغيري: (الترتيب الولادي للطالب، المستوى التعليمي للوالدين). وتكونت عينة البحث من (276) طالبا وطالبة من الصف الثاني الثانوي في محافظة دمشق. واستخدم الباحث مقياس الانتماء المدرسي ومقياس المشكلات السلوكية وهما من إعداد الباحث، واعتمد البحث على المنهج الوصفي. وخلصت الدراسة إلى النتائج الآتية: 1- وجود علاقة ارتباطية سالبة ذات دلالة إحصائية بين درجات طلبة الصف الثاني الثانوي على مقياس الانتماء المدرسي ودرجاتهم على مقياس المشكلات السلوكية. 2- وجود فروق ذات دلالة إحصائية بين إجابات طلبة الصف الثاني الثانوي على مقياس الانتماء المدرسي تبعا لمتغير الترتيب الولادي لصالح الطلبة الذين كان ترتيبهم الولادي بين أخوتهم (الأكبر)، ووجود فروق ذات دلالة إحصائية تبعا لمتغير الترتيب الولادي لصالح الطلبة الذين كان المستوى التعليمي للوالدين (الإجازة الجامعية فأعلى). 3- وجود فروق ذات دلالة إحصائية بين إجابات أفراد عينة البحث على مقياس المشكلات السلوكية تبعا لمتغير الجنس لصالح الطلبة الذكور، ووجود فروق ذات دلالة إحصائية تبعا لمتغير الترتيب الولادي لصالح الطلبة الذين كان ترتيبهم الولادي بين أخوتهم (وحيد)، ووجود فروق ذات دلالة إحصائية نبعا لمتغير الترتيب الولادي لصالح الطلبة الذين كان المستوى التعليمي للوالدين لديهم (ثانوي فما دون).
The aim of the research is to identify the level of school belonging to a sample of secondary school students. And the prevalence of behavioral problems among a sample of secondary school students. It defines the relationship between school belonging and behavioral problems. The differences between the answers of the respondents on the social belonging scale and the behavioral problems scale are defined according to the two variables: (student's birth order, educational level of parents). The research sample consisted of (276) male and female students from the second secondary grade in Damascus governorate. The researcher used the school belonging scale and the behavioral problems scale which were prepared by the researcher. The research relied on the descriptive method. The study concluded that: 1. There is a negative correlation of statistically significant between the grades of second grade secondary students on the scale of school belonging and their grades on the scale of behavioral problems. 2. There are statistically significant differences between the answers of second grade students on the school belonging scale according to the birth order variable in favor of students whose birth order was between their siblings (the elder), and the presence of statistically significant differences according to the birth order variable in favor of students who had the educational level of the parents. University degree and above). 3. There are statistically significant differences between the answers of the research sample on the behavioral problems scale according to the sex variable in favor of male students, and the presence of statistically significant differences according to the birth order variable in favor of students whose birth order was between their siblings (single), and the presence of statistically significant differences according to Of the birth order variable in favor of students whose parents' educational level was (secondary or lower).
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- علم النفس السلوكي -- المشكلات السلوكية -- التعليم الثانوي -- طلاب المرحلة الثانوية -- الإنتماء المدرسي